Prepare for the magnifying glass: SEC hikes scrutiny of asset managers – 4 steps to consider. Issue 1 (5th May 2015) - Weiner, Perrie Michael; Hunnius, Patrick; Alexander, Grant
Abstract : Purpose: – To discuss the Securities and Exchange Commission's (SEC's) likely preparation of new rules to increase the monitoring and oversight of various asset funds, including hedge funds and alternative mutual funds, and recommends protective measure for fund managers to take. Design/methodology/approach: – Discusses the SEC's increasing concerns about risks related to the asset management industry and how those concerns may lead to additional scrutiny and regulation. Recommends four steps for alternative mutual fund managers to take at this time to protect their interests. Findings: – The SEC's potential regulatory action is in response to apparent increasing concern that the multitrillion-dollar asset management industry could create substantial instability to the financial system with the occurrence of a significant event, such as a sudden change in interest rates or widespread investor redemptions. It has been suggested that the proposed sweep of alternative mutual funds is part of a larger strategy by the SEC to bring the alternative mutual funds, and similarly situated entities such as asset managers and hedge funds, under the same regulatory umbrella imposed upon large banks and similarly situated financial institutions in response to the 2008 recession. Practical implications: – Preparation will go a long way in dealing with what appears to be a developing mine field of new regulations, and potential enforcement actions, from the federal government. Originality/value: – Knowing that increasing SEC scrutiny, such as inquiries and subpoenas, may be just around the corner, the precautionary measures outlined in this article will help alternative mutual fund managers protect their interests.